A Critical Role for GRP78/BiP in the Tumor Microenvironment for Neovascularization During Tumor Growth and Metastasis - Dong, Dezheng (2011)
GRP78/BiP is a multifunctional protein which plays a major role in endoplasmic reticulum (ER) protein processing, protein quality control, maintaining ER homeostasis and controlling cell signaling and viability. Previously, using a transgene-induced mammary tumor model, we demonstrated that Grp78 heterozygosity not only impeded cancer growth through suppression of tumor cell proliferation and promotion of apoptosis, the Grp78+/− mice exhibited dramatic reduction (70%) in the microvessel density (MVD) of the endogenous mammary tumors while having no effect on the MVD of normal organs. This observation suggests that GRP78 may critically regulate the function of the host vasculature within the tumor microenvironment. In this report, we interrogated the role of GRP78 in the tumor microenvironment. In mouse tumor models where wild-type, syngeneic mammary tumor cells were injected into the host, we showed that Grp78+/− mice suppressed tumor growth and angiogenesis during the early but not late phase of tumor growth. Growth of metastatic lesions of wild-type, syngeneic melanoma cells in the Grp78+/− mice was potently suppressed. We created conditional heterozygous knockout of GRP78 in the host endothelial cells and demonstrated severe reduction of tumor angiogenesis and metastatic growth with minimal effect on normal tissue MVD. Furthermore, knockdown of GRP78 expression in immortalized human endothelial cells demonstrated that GRP78 is a critical mediator of angiogenesis by regulating cell proliferation, survival, and migration. Our findings suggest that concomitant use of current chemotherapeutic agents and novel therapies against GRP78 may offer a powerful dual approach to arrest cancer initiation, progression and metastasis.